2018
DOI: 10.1155/2018/4723167
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Patients with Squamous Cell Carcinoma of the Vulva: The Largest Series from a Tertiary Care Hospital

Abstract: Objective To evaluate the outcomes of squamous cell carcinoma (SCCA) of the vulva treated at our tertiary care center. Methods The medical records of SCCA patients treated between January 2006 and December 2015 were retrospectively reviewed. Results One hundred forty-five patients met the criteria with the median age of 57 years old, and 58.6% had an underlying disease. The distribution of stages was as follows: IA 6.2%, IB 21.4%, II 26.2%, IIIA 14.5%, IIIB 6.2%, IIIC 9.7%, IVA 9.0%, and IVB 6.9%. One hundred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The 5 years disease-free survival is 66%, which is comparable to the studies published by Sharma DN. et al [13], Singh N. et al [21], Rajshree D K. et al [22], and Meelapkij P. et al [23]. There are no large randomized controlled trials or meta-analysis because of the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The 5 years disease-free survival is 66%, which is comparable to the studies published by Sharma DN. et al [13], Singh N. et al [21], Rajshree D K. et al [22], and Meelapkij P. et al [23]. There are no large randomized controlled trials or meta-analysis because of the rarity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the difference of the study designs or different age groups and adjuvant treatment regimens. Meelapkij et al [24] examined 145 patients with vulvar SCC and detected 5-year survival rate as 50.8%. Although the study population was elder in our study, the 5-year survival rate was found to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoma of the vulva is a rare tumour, accounting for 4% of all gynaecological malignancies, with an incidence of two to seven cases per 100,000 women. In about 90% of cases the histological type is SCC [1] , which includes two aetiological subtypes with bimodal distribution. The classic type is related to human papilloma virus (HPV) infection, occurs in younger women and is associated with high-risk sexual activity.…”
Section: Discussionmentioning
confidence: 99%